Pendampingan Optimalisasi Branding Pada Produk Kue Bangkit sebagai Makanan Tradisional - Chandra, Pivit Septiary; Eka Putri, Sonia Sischa; Ilosa, Abdiana; Putra, Ilham Chanra (MENARA RIAU, 2024)
The purpose of this service is to provide assistance in optimizing branding on Kue Bangkit products to be able to maintain the sustainability of its business Kue bangkit is usually consumed as a complementary food and mandatory snack for the people of Kundur Island during religious holidays such as Eid al-Fitr, Eid al-Adha, and Chinese New Year. The prospects for traditional foods such as Kue Bangkit to develop at this time are actually quite good because such rapid communication and information technology can improve the promotion of its development. The method carried out in this devotion is the method of lectures and discussions or questions and answers. The socialization program on optimizing branding on local products Kue Bangkit typical of Kundur Islands goes through 4 stages, namely the licensing, preparation, implementation, and evaluation stages. This activity provides positive results in understanding and strengthening branding for Kue entrepreneurs rising in the Kundur area, with this activity entrepreneurs increasingly understand and can manage their business better.